Avaliação do fluxofenim nas culturas do sorgo, trigo e arroz como protetor ao herbicida s-metolachlor - Silva, João Renato Vaz da [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Este trabalho teve o objetivo de avaliar a eficiência do safener fluxofenim no tratamento de sementes de sorgo (DKB510 e SCG340), trigo (Avante e Ônix) e arroz (Bonanza e Aimoré), para o aumento da seletividade a aplicação do herbicida Smetolachlor em pré-emergência e determinar a atividade da enzima de detoxificação glutationa S-transferase (GST). O trabalho foi dividido em duas etapas. A primeira etapa constou da avaliação em campo da eficiência do safener em reduzir sintomas visuais de fitointoxicação causados pelo herbicida. Esta etapa foi conduzida na Estação Experimental pertencente à Syngenta Seeds no município de Uberlândia, Minas Gerais. Na segunda etapa foi determinada a atividade da GST, no Laboratório de Xenobióticos, do Departamento de Química e Bioquímica do Instituto de Biociências, UNESP, Campus de Botucatu, Botucatu, São Paulo. Foram comparadas a suscetibilidade ao herbicida por meio da avaliação visual de injúrias aos 3, 7, 15 e 30 dias após a emergência (DAE), massa seca de raiz e parte aérea aos 10 DAE, além da determinação da atividade da GST. Os tratamentos utilizados foram: aplicação ou não do safener na dose de 40mL por 100 kg...

This work aimed to evaluate the effectiveness of fluxofenim used for seed treatment as safener for sorghum, wheat and rice treated with the herbicide S-metolachlor applied in preemergence. The study was divided in two steps. In the first step it was measured the fluxofenim safener potential to reduce visual symptoms of S-metolachlor injury in the field. This phase was conducted in Uberlandia city, Minas Gerais, at Syngenta Experimental Station, and treatments were followed by S-metolachlor at 1.440 and 2.880 mL i.a. ha-1, and fluxofenim at 0, and 40 mL per 100 kg of seeds, and a check without treatment. The second phase was set up at Chemistry and Biochemistry Departament in Botucatu, UNESP, São Paulo, to evaluated glutathione S-transferase activity (GST) in the crops that responded to field treatments with safener. It was used two varieties/hybrids per crop and it was measured herbicide phytotoxity as visual symptoms at 3, 7, 15 and 30 days after emergence, dry matter at 10 DAE, and gluthationa S-transferase activity. Fluxofenim increased S-metolachlor tolerance for both sorghum hybrids, but best results were observed at 1.440 mL i.a. ha-1. Wheat varieties showed low tolerance to S-metolachlor in both rates, and fluxofenim increased S-metolachlor selectivity to wheat but not sufficient, reducing plant population to a non acceptable level. Seed treatment with fluxofenim for both rice varieties had no effect, and both S-metolachlor rates increased killed all plants treated with or without fluxofenim. Gluthationa S-transferase activity for sorghum and wheat increased when seeds treated with fluxofenim were submitted to S-metolachlor at 1.440 mL a.i. ha-1.
Keywords: Herbicidas; Sementes; Trigo; Sorgo; Arroz; Safener; Fluxofenim; S-metolachlor; Wheat; Sorghum; Rice